DETECTION OF PHYSIOLOGICAL LEFT VENTRICULAR HYPERTROPHY IN JUDOCA ATHLETES THROUGH THE ECO-DOPPLER (Fiep Bulletin - online, 2011)
This study aimed to determine the incidence of physiological left ventricular hypertrophy in judo, differentiating it from Hypertrophic Cardiomyopathy, and compare the anthropometric and echocardiographic variables. A cross-sectional study was conducted, consisting of a sample of 40 judoka athletes, who underwent an examination of Doppler Echo, as well as a body assessment, which included the following aspects: the fat percentage, height, body mass. The nonparametric statistical test of Mann-Whitney was used and the coefficient of linear correlation of Pearson was used to assess the level of association between the anthropometric and echocardiographic variables. It was used, also, the descriptive analysis in the form of medium and standard deviation, using the software SPSS 10.0. Of the 40 athletes, four athletes (0.1 ± 1.02) showed signs of physiological left ventricular hypertrophy (athletic heart "), with cavity diameters and ventricular thicknesses increased. By comparing athletes who presented physiological left ventricular hypertrophy and those who did not, it was found in the group with physiological left ventricular hypertrophy a significant difference in the final diameter of the left ventricle, in the left ventricular mass, in the diastolic septum thickness, in the diastolic thickness of LVPW (ventricular posterior wall), in the relation mass / body surface area and in the final diastolic volume, systolic volume, the volume / mass and end-systolic volume. It was found that the percentage of shortening of the cavity is influenced by the BMI and by the triceps fold, explaining that 18% of the shortening is influenced by the BMI and 10% of the shortening is influenced by the fold of the triceps. It was concluded that four athletes presented left ventricular concentric hypertrophy. When making a correlation of anthropometric and echocardiographic, it was found that the percentage of shortening of the cavity is influenced by the BMI and by the triceps fold, whereas the systolic volume is influenced in 10% of cases, by the percentage of fat.
Keywords: left ventricular hypertrophy; judo; athletes; Doppler Echo